Sierra Leone Public Expenditure Review 2021 : Sierra Leone Agriculture Sector Review - World Bank (World Bank, Washington, DC, 2021)
At the request of the Government of Sierra Leone (GoSL), the World Bank is undertaking a programmatic Public Expenditure Review (PER) to analyze fiscal policy quality and provide policy advice to the GoSL with a focus on fiscal policy and public financial management. The analysis is also meant to inform World Bank projects and operations, other development partners, and the public. The activities of the Programmatic PER are and organized in two modules. The first module is an overview of public expenditure and a fiscal sustainability analysis. More specifically, it analyzes the composition of the budget (based on economic and functional classification) and fiscal sustainability and risks. The second module of the PER is comprised of four sector specific analyses: (i) health, (ii) education (iii) social protection, and (iv) agriculture. The selection of the specific sectors has been motivated by their low level of public spending (in absolute and relative terms), except for health, and low spending efficiency scores the country experiences in these sectors. The Agriculture Sector Public Expenditure and Institutional Review (AgPEIR) therefore constitutes part of the second module of the Programmatic PER. The AgPEIR covers core issues related to the level and quality of public spending in agriculture, which will help to identify the pathway to fiscal adjustment and management of medium to long-term expenditure constraints identified from the previous administration’s budgetary details. The agriculture sector review identifies existing patterns of expenditures in core agriculture-related services and the functional institutional capacities in the sector. It is intended to help the new administration make evidence-based decisions on resource allocation by identifying historical patterns of expenditure, comparing these with sector achievements, and suggesting areas for improvements in expenditure management in the future.